Autoimmune epilepsy in children: Case series and proposed guidelines for identification. (28th March 2013) - Suleiman, Jehan; Brilot, Fabienne; Lang, Bethan; Vincent, Angela; Dale, Russell C.
Summary Purpose Antibodies against neuronal surface proteins are increasingly recognized in autoimmune central nervous system (CNS) disorders in which seizures are the main or an important feature. The disorders include antibody‐associated limbic encephalitis and N‐methyl‐D‐aspartate receptor (NMDAR)encephalitis; however, seizures of autoimmune etiology may exist beyond the spectrum of these recognized syndromes. Because these seizures are potentially treatable with immune therapy, guidelines are needed to help in their early recognition. Methods We describe 13 representative children seen at our tertiary institution over a period of 3.5 years with suspected autoimmune epilepsy. Autoimmune epilepsy was suspected clinically when there was any of the following: (1) recognizable syndromes such as NMDAR encephalitis or limbic encephalitis, (2) evidence of CNS inflammation in cerebrospinal fluid or on magnetic resonance imaging (MRI), (3) the presence of other autoimmune diseases, or (4) positive response to immunotherapy. We tested these patients for neuronal surface antibodies (voltage gated potassium channel [VGKC]‐complex, leucine rich glioma inactivated 1 [LGI1], contactin‐associated protein‐like 2 [CASPR2], and NMDAR) and glutamic acid decarboxylase (GAD) antibodies. We modified the J Neurol Neurosurg Psychiatry, 83, 2012, 638 guidelines that were designed to classify adults with neuronal surface antibody syndromes (NSAS), to be more appropriate for children with suspected autoimmune epilepsy. Using the modified guidelines, the 13 patients were classified into definite, probable, possible, unlikely, or unknown autoimmune epilepsy according to the presence of neuronal surface or GAD antibodies, and the response to immune therapy when given. Key Findings Of the 13 patients, 11 were females, and the mean age was 6 years (range 1–13 years). Three patients had classical NMDAR encephalitis, two had VGKC encephalitis, two had limbic encephalitis with negative antibodies, three had epilepsy with other autoimmune diseases (one with high titer GAD antibodies), two had fever‐induced refractory epileptic encephalopathy in school‐aged children (FIRES), and one epileptic encephalopathy associated with VGKC antibodies. Seven patients of the 13 children with suspected autoimmune epilepsy were positive for neuronal surface antibodies (NMDAR, n = 3; VGKC‐complex, n = 3; and GAD, n = 1). Immunotherapy was given to nine cases, and a positive response was more common in patients with positive neuronal surface antibodies (5/5) compared to those with negative antibodies (2/4). Applying the proposed guidelines, the classification of autoimmune epilepsy was definite in five, probable in one, possible in three, unlikely in two, and unknown in two patients. Significance Neuronal surface antibodies and GAD antibodies are present in a proportion of children with suspected autoimmune epilepsy and may define a treatable subgroup of childhood epilepsy. The proposed guidelines can be useful in the recognition of children with seizures of autoimmune etiology.